professional responsibility, cognitive, emotional, and behavioral components of effective professional liability, professional liability structure, subject, object, instance of responsibility, personal-situational approach. - Stavitskiy, Oleg (Psychological Prospects Journal, 2015)
The article is devoted to the analysis of the psychological attitude towards  people with disabilities. The  article  reveals  and  clarifies the  concept   of«handicapism» as a social phenomenon that is updated by the negative perceptions of disabled people. The results of empirical research  of  handicapism aspects  obtained with the help of a questionnaire which is valid and tested are represented. The attitude towards disabled is shown through their perception of the parameters such   as: anger, depression, disgust, contempt, fear, hostility, anxiety, selfishness, desire to dominate, aversion, intolerance, prejudice, poor empathy. Analysis of the results allowed us to determine that a significant proportion of people with disabilities perceive the treatment of others as neutral, as evidenced by the dominance of the average level for most scales. A minority of disabled  notes  that  surrounding  treat them positively, but there are respondents who say that society does not accept  them, reveals hostility, intolerance, perceives bias. Special attention was paid to the consideration of such data, as it indicates that people with disabilities experience signs  of  handicapism  on  the  part  of  society.  The  highest  rates  were  on scales«Dislikes», «Biased» and «Underdeveloped empathy». This indicates that disabled respondents especially acutely are aware of the negative attitude of society towards them, suffer from the inadequacy of their assessment, stereotypes about disabled and  the inability of society to understand a person with disabilities, to reveal sympathy.
Keywords: society, setting, disability, disabled, handicapism